POLYNEUROPATHY ARISING IN THE COURSE OF GOUT- A CASE REPORT - Özlem YOLERİ,; Berrin ÖNGEN,; İlker ŞENGÜL,; Neşe ÖLMEZ,; Asuman MEMİŞ,; Figen EŞMELİ, (Archives of Rheumatology, 2005)
Polyneuropathy arising in the course of gout may be due to various reasons. Colchicine intake, alcohol abuse and vitamin B12 deficiency are among these. A 65-year-old male patient has been reported to remind the physicians the reasons underlying the polyneuropathy seen in gouty arthritis and emphasize the difficulty of a differential diagnosis.